2014
DOI: 10.1038/cddis.2014.323
|View full text |Cite
|
Sign up to set email alerts
|

Severe influenza A(H1N1)pdm09 infection induces thymic atrophy through activating innate CD8+CD44hi T cells by upregulating IFN-γ

Abstract: Thymic atrophy has been described as a consequence of infection by several pathogens including highly pathogenic avian influenza virus and is induced through diverse mechanisms. However, whether influenza A(H1N1)pdm09 infection induces thymic atrophy and the mechanisms underlying this process have not been completely elucidated. Our results show that severe infection of influenza A(H1N1)pdm09 led to progressive thymic atrophy and CD4+CD8+ double-positive (DP) T-cells depletion due to apoptosis. The viruses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 48 publications
(82 reference statements)
6
62
0
Order By: Relevance
“…Because conducting research investigations on the thymuses of HIV-infected humans (Verinaud et al 2004) is difficult, many animal model systems have been developed. The simian immunodeficiency virus (SIV)-infected monkey model is much better than the feline and murine models, on the basis that this species not only acts as a natural host for the infection, but also offers Duan et al 2015;Hu et al 2016;Liu et al 2014 Parasites…”
Section: Pathogenic Infections and Ati Viral Infections And Atimentioning
confidence: 99%
See 2 more Smart Citations
“…Because conducting research investigations on the thymuses of HIV-infected humans (Verinaud et al 2004) is difficult, many animal model systems have been developed. The simian immunodeficiency virus (SIV)-infected monkey model is much better than the feline and murine models, on the basis that this species not only acts as a natural host for the infection, but also offers Duan et al 2015;Hu et al 2016;Liu et al 2014 Parasites…”
Section: Pathogenic Infections and Ati Viral Infections And Atimentioning
confidence: 99%
“…This study demonstrated that use of an antiviral drug was ineffective whereas inhibition of CD8 + cells could reverse the thymic involution. This unique mechanistic insight might therefore lead to better preventive measures as well as a therapeutic tool to reverse the influenza A(H1N1)pdm09-induced ATI (Liu et al 2014). Very recently, in vitro and in vivo studies demonstrated that oral administration of phenylethanoid glycosides extracted from Ligustrum purpurascens has a protective effect that involved increasing the production of IFN-γ in IFN-γ knockout mice during an infection with H1N1 (Hu et al 2016).…”
Section: Paracoccidioides Brasiliensismentioning
confidence: 99%
See 1 more Smart Citation
“…versus mock-infected). IFN-c is a key cytokine involved in the protective immune response against various pathogen infections (Flynn et al, 1993;Julkunen et al, 2001), but has also been shown to participate in the induction of pathological courses, especially thymic atrophy and T-cell depletion during viral or bacterial infections (Borges et al, 2012;Deobagkar-Lele et al, 2013;Liu et al, 2014).…”
Section: Nk-cells Were Activated By Influenza Virus Infectionmentioning
confidence: 99%
“…Trypanosoma cruzi, Plasmodium chaubi) and fungal infections (exemplified by experimental infections with Paracoccidioides brasiliensis and Histoplasma capsulatum) (Savino, 2006). To date, several mechanisms have been implicated in influenza virus infection-induced thymic atrophy, such as interference with T-lymphocyte development, increased levels of glucocorticoids and elevated IFN-c production by innate CD8 + T-cells (Liu et al, 2014;Tian et al, 2012;Vogel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%